Neuropharmacological characteristics of antidepressant action of a new 3-substituted thietane-1,1-dioxide derivative - Irina L. Nikitina; Gulnara G. Gaisina (Belgorod National Research University, 2021)
Introduction: Due to severe burden of depressive disorders and a low rate of remission in patients receiving antidepressant therapy, there is an urgent need for developing novel agents with antidepressant action and a fundamentally new mechanism of action. 3-ethoxythietane-1,1-dioxide (N-199/1) is a new molecule that showed significant antidepressant properties when administered intraperitoneally once or repeatedly. The aim of the present study was to investigate the mechanism of action of N-199/1, using reserpine test. Materials and methods: N-199/1 (2 mg/kg and 4.86 mg/kg) and the reference drugs (imipramine and fluoxetine) were administered once intraperitoneally to outbred male mice 4 h (Experiment 1) and 18 h (Experiment 2) after a single intraperitoneal injection of reserpine (2.5 mg/kg). The severity of reserpine-induced symptoms (hypothermia, ptosis and akinesia) was assessed. Results and discussion: N-199/1 potentiated reserpine-induced hypothermia at both doses and reduced ptosis at a dose of 2 mg/kg when administered 4 h after reserpine. N-199/1 increased the duration of reserpine akinesia at a dose of 2 mg/kg when administered 18 h after reserpine and at a dose of 4.86 mg/kg when administered 4 h after reserpine. The effect of N-199/1 resembled the effect of fluoxetine and was dose-dependent. Conclusion: Based on the results obtained, it can be assumed that the antidepressant action of N-199/1 is due to its serotonin-positive properties, and probably the blockade of serotonin 5HT2A/2C receptors and/or α2-adrenergic receptors. The effect of N-199/1 is dose-dependent and resembles the effect of fluoxetine. Graphical abstract: